Functional Impact of Sydenham's Chorea: A Case Report. (26th March 2013) - Gimeno, Hortensia; Barry, Sinead; Lin, Jean-Pierre; Gordon, Anne
Background: Sydenham's chorea (SC) is the most common type of acquired chorea in childhood. In some cases, symptoms (most commonly described in terms of neurological signs) last up to 2 years, and many cases relapse. This report describes the clinical course in terms of functional abilities following diagnosis of SC. Case report: Standardized assessments across the domains of activity and participation were administered following diagnosis, prior to and following treatment with haloperidol to measure treatment response and identify occupational therapy intervention needs. SC was observed to significantly reduce the child's participation and independence in activities of daily living. In this case, the standardized assessments administered highlighted difficulties with both motor and process skills. At 1 week after commencing haloperidol, both motor and process skills had improved. Clinically significant changes in self-care and mobility were noted with less improvement with handwriting. At 9 weeks, most symptoms and functional difficulties had resolved. Discussion: Given the process difficulties detected in this case, and the possibility of enduring symptoms, the use of functional assessments is advocated in the routine management of SC. These findings illustrate the potential for motor and non-motor sequelae in acute childhood movement disorders and related functional disabling consequences.